2021
DOI: 10.1002/agt2.92
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic carrier transports and low thermal conductivity in n‐type layered InSe thermoelectrics

Abstract: Semiconductor InSe with wide bandgap and layered crystal structure is expected to be a promising thermoelectric material, and its excellent plasticity brings great potential applications in flexible and wearable thermoelectric devices. To advance its thermoelectric performance, this work systematically investigates the carrier and phonon transport properties in n‐type InSe. It is found that InSe compound presents an exceptional dynamic carrier transport property due to the amphoteric indium (In+ and In3+), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…[ 70,71 ] We note that these thicknesses and lateral tip displacements are larger than the corresponding phonon mean free path λ of γ‐InSe, which is of the order of 3 nm, as reported elsewhere. [ 72 ] The upper bound of the mean free path for γ‐InSe can also be estimated using the kinetic model (λ = 3 k z C v −1 υ s −1 ) where υ s is the speed of sound, C v is the volumetric heat capacity [ 73 ] and k z are the literature reported thermal conductivity values of layered γ‐InSe (≈2 Wm −1 K −1 ). [ 27,41,73 ] This results in a mean free path λ < 5 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 70,71 ] We note that these thicknesses and lateral tip displacements are larger than the corresponding phonon mean free path λ of γ‐InSe, which is of the order of 3 nm, as reported elsewhere. [ 72 ] The upper bound of the mean free path for γ‐InSe can also be estimated using the kinetic model (λ = 3 k z C v −1 υ s −1 ) where υ s is the speed of sound, C v is the volumetric heat capacity [ 73 ] and k z are the literature reported thermal conductivity values of layered γ‐InSe (≈2 Wm −1 K −1 ). [ 27,41,73 ] This results in a mean free path λ < 5 nm.…”
Section: Resultsmentioning
confidence: 99%
“…[70,71] We note that these thicknesses and lateral tip displacements are larger than the corresponding phonon mean free path λ of γ-InSe, which is of the order of 3 nm, as reported elsewhere. [72] The upper bound of the mean free path for γ-InSe can also be estimated using the kinetic model…”
Section: Xsthm Heat Transport Measurementsmentioning
confidence: 99%
“…Si doping can decrease the average RT κ to a very small value of 1.6 W m −1 K −1 [141]. The κ of InSe 0.95 S 0.05 is ∼0.6 W m −1 K −1 at 723 K [142]. That suggested that there is a large space to modulate the κ of 2D InSe.…”
Section: Experimental Work On the Thermal Conductivity Of 2d Insementioning
confidence: 97%
“…Layered InSe has gained considerable attention because of its potential applications in flexible thermoelectric devices stemming from exceptional deformability and plasticity. , For its monolayer counterpart, many researchers have demonstrated the excellent thermoelectric performance and investigated the possibility of improving the performance through external stimuli. For its bulk counterpart, it is well-known that there exist three different polytypes characterized by the arrangement of the layers, which are described as β-, ε-, and γ-polytypes. The β- and ε-polytypes belong to the hexagonal system, while the γ-polytype has rhombohedral symmetry. Previous studies mainly focused on the optimization of the carrier concentration and mobility of β-InSe, while the thermoelectric properties of γ-InSe, not to mention the effect of pressure on the electronic and thermal transport properties in γ-InSe, are rarely addressed.…”
Section: Introductionmentioning
confidence: 99%